جريمة اثارة الحرب الاهلية او الاقتتال الطائفي (دراسة تحليلية قانونية) - البدراني, . طلال عبد حسين; سطام, : محمد ذياب (Journal of Legal Sciences, 2019)
The crime of provoking the civil war and  the sectarian conflict  is considered the most dangerous crimes threatened the interior security of the state and its stability, thus most of the punitive laws legislated punishment on them and the Iraqi penal code criminated it in article(195) also Iraqi anti-terrorist law in its item(4) of article (2), and the legislator has illustrated that this crime has multiple forms, happens only by committing one of them, and the law does not require committing all of them together to set up the  criminal liability of its perpetrator, and he illustrated that  it is committed via arming the citizens or forcing them to be armed or  urging of fighting, here the criminal legislator has linked some of the material side forms with the arm, and the criminal is aiming to realize certain aim, and limited with the text of instigating the civil war and the sectarian conflict, and the punitive text does not requires to occur actually of the  perpetrator, where the punishment lies on him and does not occurs of what he does not want to be happened, and if it is happened actually or caused others to be armed of individuals , then this would effect only of the punishment amount , that its punishment reached its utmost limit which is the execution, and the law has specified provisions concerned pardoned from punishment.               This crime has its certain provisions specified by the law and focused on it  compared with the other crimes of interior security of the state, and this has become clear via exceptions of the criminal law regional principle and subjecting it with other crimes of the interior and the external security of the state and some of the crimes specified by the text for the in-king principle of the criminal law, the exception of the general origin of the regional of the law principle, on the other hand, the law has becomes away from the provisions of general affiliation contribution  crimination provisions and with in specific texts, and it has become clear that that this crime is regarded the most dangerous crime which the law and their legislators aware of it for the safety of the humanitarian  communities and their stability, also what we have see today in our  country of threats and actual threats signaling of  civil and sectarian conflicts in our dear country to disseminate destruction and dividing the society in to conflicting groups tearing the national unity of the people and cohesion and the historical harmony known by our society for deep in the history.